UPAYA PELESTARIAN SILAT PERISAI DI BANGKINANG KABUPATEN KAMPAR PROVINSI RIAU - Nike Suryani; Muslim Muslim (Universitas Andalas, 2020)
Preservation efforts as activities or carried out continuously, directed and integrated to realize certain goals that reflect the existence of something that is permanent and eternal. Silat Shield is one of the traditions in Kampar District that needs to be preserved. The purpose of this study looks at the form of Shield Silat and Shield Silat Preservation Efforts in the District of Bangkinang, Kampar Regency. The theory in this writing can be put forward in the opinion of Hadiwanto Conservation must live and develop in the community. Conservation must be fought by the wider community. Chaedar alwasilah said there were three steps, namely: (1) understanding to generate awareness, (2) collective planning, and (3) creativity generation. This research method is a type of research used is qualitative with the Phenomenology approach. Data collection techniques by observation, interview and documentation. Keywords:Tradition, Silat Perisai, Preservation efforts